Entering construction professionals: survey of work values and career expectations - Moore, Jennifer Dawn, author; Guggemos, Angela A., advisor; Khattab, Mostafa, committee member; Gloeckner, Gene W., committee member (Colorado State University. Libraries, 2011)
The discussion of human resources is a broad and complex one, especially in an industry as diverse as construction which employs unskilled and skilled crafts workers, clerical and professional staff, as well as a variety of construction professionals. With an understanding that employers must develop more effective ways of rewarding and developing their workforces to compete for new hires and retain their current personnel, the goal of this research is to give those construction organizations focused on strategic human resource management a better understanding of the individuals currently entering the workforce. The general research design of this study was a comparative and associational research approach or a non-experimental approach. In this particular case, this research design was appropriate as the study was centered on defining work values and career expectations of soon-to-be Construction Management graduates as related to their personal characteristics. As such, the intention of the survey employed was twofold. One aspect was to gain a personal profile of these individuals and an assessment of what values these entering construction professionals hold. The second piece was to examine this descriptive data and seek an understanding into any relationships which may exist among the personal characteristics of entering construction professionals and their stated life, behavioral, and work values. From this sample some general trends of this population were found. A review of the mean rankings of life and behavioral values shows the values associated as self-centered ranked highest of all values while social-centered were lowest. Instrumental values of moral-focused and competence-focused ranked between these two terminal values and were nearly identical. The work values associated with status and independence ranked above those associated with competence and growth and comfort and security. Those in the construction industry must recognize that the graduates of today are different than those of past generations and that what it takes to hire and retain these individuals is different than the strategies employed even a decade ago. Likewise, for the first time in American history, companies are challenged with managing four generations of employees at once, each with different values, expectations, and attitudes. For the industry to continue to grow and prosper, the leaders of tomorrow must be recruited and trained today and companies must identify a leadership succession plan, placing renewed emphasis on strategic human resource management.
Keywords: career; construction; expectations; industry; values; work